THEORETICAL ASPECTS OF THE MECHANISM OF FUNCTIONING OF THE INDUSTRIAL ENTERPRISES - Firuza A. Atabaeva (Статистика и экономика)
In this article the theoretical foundations of the functioning of industrial enterpriseswas considered and the management ofmechanism was suggested in deﬁnition which based on the elements of the institutional (the structure of state support,legislative support structure), prices, supply, demand, competition and technology. The structure was suggested to separateon organizational structure-functional,ﬁnancial-economic and legal unit